A critical review of the application of polymer of low concern and regulatory criteria to fluoropolymers. (30th March 2018) - Henry, Barbara J; Carlin, Joseph P; Hammerschmidt, Jon A; Buck, Robert C; Buxton, L William; Fiedler, Heidelore; Seed, Jennifer; Hernandez, Oscar
ABSTRACT: Per‐ and polyfluoroalkyl substances (PFAS) are a group of fluorinated substances that are in the focus of researchers and regulators due to widespread presence in the environment and biota, including humans, of perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA). Fluoropolymers, high molecular weight polymers, have unique properties that constitute a distinct class within the PFAS group. Fluoropolymers have thermal, chemical, photochemical, hydrolytic, oxidative, and biological stability. They have negligible residual monomer and oligomer content and low to no leachables. Fluoropolymers are practically insoluble in water and not subject to long‐range transport. With a molecular weight well over 100 000 Da, fluoropolymers cannot cross the cell membrane. Fluoropolymers are not bioavailable or bioaccumulative, as evidenced by toxicology studies on polytetrafluoroethylene (PTFE): acute and subchronic systemic toxicity, irritation, sensitization, local toxicity on implantation, cytotoxicity, in vitro and in vivo genotoxicity, hemolysis, complement activation, and thrombogenicity. Clinical studies of patients receiving permanently implanted PTFE cardiovascular medical devices demonstrate no chronic toxicity or carcinogenicity and no reproductive, developmental, or endocrine toxicity. This paper brings together fluoropolymer toxicity data, human clinical data, and physical, chemical, thermal, and biological data for review and assessment to show that fluoropolymers satisfy widely accepted assessment criteria to be considered as "polymers of low concern" (PLC). This review concludes that fluoropolymers are distinctly different from other polymeric and nonpolymeric PFAS and should be separated from them for hazard assessment or regulatory purposes. Grouping fluoropolymers with all classes of PFAS for "read across" or structure–activity relationship assessment is not scientifically appropriate. Integr Environ Assess Manag 2018;14:316–334. © 2018 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals, Inc. on behalf of Society of Environmental Toxicology & Chemistry (SETAC) Key Points: Fluoropolymers, for example, polytetrafluoroethylene (PTFE), satisfy widely accepted criteria to be considered polymers of low concern (PLC). Their physical–chemical properties prevent bioavailability, bioaccumulation, toxicity, and degradation. They have negligible monomer, oligomer, leachables, or reactive functional group content. Fluoropolymers are not Persistent Organic Pollutants (POPs), per the Stockholm Convention on POPs, persistent bioaccumulative toxic (PBT), or very persistent very bioaccumulative (vPvB), or mobile as the German Umweltbundesamt (UBA) proposed. They are benignly persistent (highly stable, inert); are not water soluble, toxic, or bioaccumulative; and they lack leachable substances of toxicological concern. Perfluoroalkyl and polyfluoroalkyl substances (PFAS) are a large group of fluorinated chemicals with diverse properties. A single, globally harmonized system for PFAS classification has not yet been defined, resulting in lack of recognition of important distinctions between PFAS. Fluoropolymers exhibit common thermal, physical, chemical, and biological characteristics and are a distinct class of polymeric PFAS. Toxicity data, human clinical data, physical–chemical data, and chemical analyses confirm their low hazard and distinct difference from other classes of PFAS.